Integrating Islamic Criminal Law and Indonesian Law in Sentencing Narcotics Offenders: Comparative Reformulation in Bungo Regency - Panji Lanjuardi; Bahrul Ulu; Hermanto Harun; Abdul Halim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to examine the normative construction and practical implementation of criminal sanctions against narcotics abusers from the perspectives of Islamic criminal law and Indonesian positive law, as well as to formulate an integrative policy model that is more just, humane, and context-sensitive in Bungo Regency. Narcotics abuse constitutes a multidimensional problem involving legal, social, moral, and public health dimensions. Therefore, a comprehensive approach is required to integrate the normative values of Islamic criminal law with the national legal system. This research employs a normative-empirical approach using comparative legal analysis, examining statutory regulations, doctrines of Islamic criminal law, and law enforcement practices at the local level. The findings indicate that Islamic criminal law frames narcotics abuse within the protection of maqāṣid al-sharī‘ah, particularly the preservation of intellect (ḥifẓ al-‘aql) and life (ḥifẓ al-nafs), thereby emphasizing not only punitive but also educational and rehabilitative orientations through the instrument of ta‘zīr. Meanwhile, Indonesian positive law, particularly Law No. 35 of 2009 on Narcotics, provides legal space for rehabilitation; however, its implementation still encounters structural and cultural challenges. This study concludes that integrating Islamic criminal law principles with the national legal framework may produce a more responsive sentencing model that upholds substantive justice, human rights protection, and effective narcotics control. Policy reformulation grounded in religious values, restorative approaches, and social rehabilitation is recommended as a strategic direction for national criminal law reform.